2021
DOI: 10.3390/fermentation7040262
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Antioxidant Peptides from Thai Traditional Semi-Dried Fermented Catfish

Abstract: Herein, the antioxidant peptides from a Thai traditional semi-dried fermented farmed hybrid catfish (Clarias macrocephalus × Clarias gariepinus) catfish, Pla Duk Ra, were characterized. After extraction and deproteinization, Pla Duk Ra crude peptide extract (CPE) was fractioned using 2 connected Hitrap Sephadex-G25 columns, yielding two significant fractions, F1 with higher browning intensity (A420) and F2. CPE, F1, and F2 had different amino acid profiles, contents, and sequences evaluated by LC-MS/MS, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…In this study, cysteine, glycine, arginine, histidine, and proline were significantly different (p < 0.05) among fractions. Our results were consistent with the finding of Chaijan et al (2021), who reported that a high content of these AAs enhanced the DPPH and ABTS radical scavenging activity of peptides. However, significant DPPH and ABTS radical scavenging activities were observed from different fractions.…”
Section: Antioxidant Properties Of Tuna Cooking Juice Concentrate Hyd...supporting
confidence: 93%
See 1 more Smart Citation
“…In this study, cysteine, glycine, arginine, histidine, and proline were significantly different (p < 0.05) among fractions. Our results were consistent with the finding of Chaijan et al (2021), who reported that a high content of these AAs enhanced the DPPH and ABTS radical scavenging activity of peptides. However, significant DPPH and ABTS radical scavenging activities were observed from different fractions.…”
Section: Antioxidant Properties Of Tuna Cooking Juice Concentrate Hyd...supporting
confidence: 93%
“…Based on our results, it is likely that not only the AA contents affected the free radical scavenging activity of the VD fraction. Other factors, such as AA sequences, the stereoselectivity of radicals, and the stoichiometry between radicals and antioxidants, may be associated with antioxidant activities (Borawska et al, 2015;Chaijan et al, 2021). In this study, the sum of AAA (tyrosine and phenylalanine) and PCAA (histidine, arginine, and lysine) content was the highest in VD-1, followed by respectively (28.76,28.54,and 24.33 g/100 g protein, respectively).…”
Section: Antioxidant Properties Of Tuna Cooking Juice Concentrate Hyd...mentioning
confidence: 50%
“…The enzyme system produced by Aspergillus niger enzymatically cleaves wheat germ proteins to amino-acid-residue-exposed polypeptides, which are more favorable for binding to the moiety and acting activity. The antioxidant peptides extracted from traditionally semi-dried fermented fish in Thailand exhibit significant efficacy in suppressing free radicals and reactive oxygen species (ROS) [43]. This observed effect may be attributed to the presence of hydrophobic and aromatic amino acids within these peptides.…”
Section: Discussionmentioning
confidence: 99%
“…These peptides are further broken down by the proteases secreted from microorganisms to form small peptides, which are subsequently converted to free amino acids by the peptidases released upon cell lysis (Candogan & Acton, 2004; Patcharin et al., 2006). Among the peptides generated during fish fermentation, some exhibit important health‐promoting properties such as antibacterial effect (Mirzapour‐Kouhdasht et al., 2021), antioxidant activity (Chaijan et al., 2021) and antihypertensive function (Itou et al., 2007; Ryan et al., 2011). It is of high interest to study the relationships among the microorganisms, enzymes, and their metabolites or enzymatic reaction products for tailoring the fish fermentation process to yield target compounds.…”
Section: Microbiome Of Traditional Fermented Fish Productsmentioning
confidence: 99%